Sperm chromatin structure assay results after swim-up are related only to embryo quality but not to fertilization and pregnancy rates following IVF - Niu, Zhi-Hong; Shi, Hui-Juan; Zhang, Hui-Qin; Zhang, Ai-Jun; Sun, Yi-Juan; Feng, Yun (Asian journal of andrology, 2011)
The aim of this study was to investigate whether the sperm chromatin structure assay （SCSA） results after swim-up are related to fertilization rates, embryo quality and pregnancy rates following in vitrofertilization （IVF）. A total of 223 couples undergoing IVF in our hospital from October 2008 to September 2009 were included in this study. Data on the IVF process and sperm chromatin structure assay results were collected. Fertilization rate, embryo quality and IVF success rates of different DNA fragmentation index （DFI） subgroups and high DNA stainability （HDS） subgroups were compared. There were no significant differences in fertilization rate, clinical pregnancy or delivery rates between the DFI and HDS subgroups. However, the group with abnormal DFI had a lower good embryo rate. So, we concluded that the SCSA variables, either DFI or HDS after swim-up preparation, were not valuable in predicting fertilization failure or pregnancy rate, but an abnormal DFI meant a lower good embryo rate following IVF.